1982
DOI: 10.1093/jn/112.3.416
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Some Xenobiotics on Ascorbic Acid Metabolism in Rats

Abstract: The administration of xenobiotics, PCB, DDT, or aminopyrine to rats causes a marked increase in urinary excretion of ascorbic acid and in various tissue levels of ascorbic acid. When rats were fed diet containing 200 ppm PCB or 500 ppm DDT (14 days), the incorporations from D-(U-14C) glucose into ascorbic acid in liver were significantly increased. The dietary addition of 200 ppm PCB, 500 ppm DDT, 2,000 ppm pentobarbital or 3,000 ppm chloretone caused a significant increase in the activity of hepatic UDPglucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(14 citation statements)
references
References 29 publications
2
12
0
Order By: Relevance
“…1A). It is known that the ascorbic acid formation increases when the rats are exposed to xenobiotics to metabolize and excrete into urine (36). A large amount of PaA administration to the rats did not induce the formation of ascorbic acid (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…1A). It is known that the ascorbic acid formation increases when the rats are exposed to xenobiotics to metabolize and excrete into urine (36). A large amount of PaA administration to the rats did not induce the formation of ascorbic acid (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…Administration of these xenobiotics increases liver ascorbic acid concentration and its urinary excretion in rats. The formation of D-glucuronate from UDP-glucose is rate-limiting in ascorbic acid synthesis because the activities of UDP-glucose dehydrogenase, which cata- lyzes UDP-glucuronate formation from UDP-glucose, and UGT but not L-gulono-␄-lactone oxidase, are elevated by some xenobiotics such as PCB and DDT in rats (34,35). Because ␀-glucuronidase activity is elevated by PCB, DDT, chloretone or aminopyrine (34), some xenobiotics may stimulate ascorbic acid synthesis by the induction of a UGT/␀-glucuronidase-mediated pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Horio et al have reported that the induction of uridine 5â€Č‐diphospho‐glucuronosyltransferase (UGT) in rats treated with phenobarbital and 3‐MC caused an increase in AsA levels in the liver, and AsA excretion in the urine was higher 6. It has also been reported that supplementation with several xenobiotics stimulates the activities of DME and AsA biosynthesis in rats 5,10,11. However, the mechanisms whereby AsA is involved with xenobiotic‐metabolizing enzymes are poorly understood.…”
Section: Introductionmentioning
confidence: 99%